Moldova Health Transformation Project : Fiduciary Systems Assessment Report - World Bank (Washington, DC, 2014)
The fiduciary systems assessment has been carried out in accordance with OP / BP 9.00 to determine whether the Program fiduciary systems provide reasonable assurance that the Program expenditures will be used appropriately to achieve their intended purposes. The findings of the fiduciary assessment conclude that the overall fiduciary and governance framework is adequate to support the implementation of the proposed Health Transformation Program for Results (HTP) and includes a summary table of the key risks and corresponding mitigation actions to be undertaken. The Program s fiduciary systems and institutions provide reasonable assurance that the financing under the Program is used for intended purposes, with due regard to the principles of economy, efficiency, effectiveness, transparency and accountability. Specifically, Moldova s fiduciary management systems for the Program (planning, budgeting, accounting, procurement, internal controls, funds flow, financial reporting, and auditing arrangements) provide a reasonable assurance on the appropriate use of Program funds and safeguarding of its assets. Furthermore, the Program s fiduciary management systems perform at a satisfactory level to support the achievement of Program results.